Cloning of the chromosome translocation breakpoint junction of the t(14;19) in chronic lymphocytic leukemia. - McKeithan, T W (1987)
Our laboratory has reported that t(14;19)(q32; q13.1) is a recurring translocation in the neoplastic cells of patients with chronic lymphocytic leukemia. In the present study, we have analyzed the leukemic cells from one such patient with probes from the immunoglobulin heavy-chain locus, which is present on band q32 of chromosome 14. Using a probe for the alpha constant-region gene segments, we detected a rearranged band by Southern blot analysis. This rearranged band was cloned and mapped. A subclone free of repetitive sequences was shown to be from chromosome 19 by analysis of human-mouse somatic cell hybrids, confirming that the rearranged band contains the translocation breakpoint junction. This probe may be used to identify a gene on chromosome 19 adjacent to the breakpoint that can contribute to the malignant development of B lymphocytes.